Green Synthesis and Characterization of Silver Nanoparticles Using Rice (Oryza sativa) and Spent Coffee (Coffea robusta) Grounds from Agricultural Waste§ - Nithiskanna Nallusamy; Nurul Afifah Mohd Kamal Rufadzil; Jasvini Bala Murally; Jing Zhi Liam; Wan Nor Dalila Wan Fauzi; Hawa Dalily Mohd Jefri; Al-Ashraf Abdullah Amirul; Seeram Ramakrishna; Sevakumaran Vigneswari (Food Technology and Biotechnology, 2025)
Research background. Silver nanoparticles (AgNPs) were synthesised using agricultural waste and green synthesis, a sustainable alternative to traditional synthesis techniques that require hazardous chemicals and extensive processing. The AgNPs were produced using spent coffee (Coffea robusta) grounds and rice (Oryza sativa) husks, both common agricultural wastes rich in bioactive substances such as proteins, flavonoids and phenolic acids that act as natural reducing agents. Experimental approach. The formation and stability of AgNPs were confirmed using various methods. UV-Vis spectroscopy showed surface plasmon resonance (SPR) peaks at 450 nm, indicating the formation of AgNPs, while Fourier transform infrared spectroscopy (FTIR) identified functional groups responsible for the bio-reduction and stabilisation of the nanoparticles. X-ray diffraction spectroscopy (XRD) confirmed the crystalline, face-centred cubic structure. Zeta potential analysis showed a stable dispersion and particle size analysis showed a consistent size distribution. The antibacterial activity of AgNPs was evaluated by testing their effectiveness against both Gram-positive and Gram-negative bacteria. Results and conclusions. The AgNPs were synthesised using spent coffee grounds and rice husks, which are rich in biomolecules that serve as effective reducing and stabilising agents. FTIR analysis identified functional groups involved in the reduction and stabilisation of nanoparticles, while XRD confirmed their face-centred cubic (FCC) crystalline structure. Zeta potential measurements showed stable dispersions with particle sizes of AgNPs obtained using spent coffee grounds of approx. 187 nm and of AgNPs obtained using rice husks of 198 nm. The synthesised AgNPs also showed strong antibacterial activity against both Gram-positive and Gram-negative bacteria. Novelty and scientific contribution. AgNPs were obtained by green synthesis using agricultural waste such as spent coffee grounds and rice husks as natural reducing and stabilising agents. This study highlights the innovative use of biomolecule-rich materials to generate stable AgNPs with strong antibacterial properties and provides a sustainable basis for further development of nanotechnological applications.